Modelación hidrológica para cuantificar la producción de agua y sedimento actual y futuro a partir de cambios de cobertura forestal, sector Prusia, Parque Nacional Volacán Irazú. - Valverde-Gamboa, Evelyn Daniela (Instituto Tecnológico de Costa Rica, 2018)
This study was conducted in the Prusia Sector, Irazú Volcano National Park, Cartago, Costa Rica. The sub-basin analyzed has an extension of 14,44 km2 and is part of the sub-basin of the Reventado River. The objective was to evaluate the changes in the production of water and sediment under different scenarios of forest cover change. The SWAT hydrological model was used to evaluate the behavior of water and sediment production. For the forest cover change, two scenarios were considered, the first was to eliminate the forest plantations and leave the ground uncovered and the second was eliminate forest plantations and let vegetation regenerate naturally. The results indicated that water production suffered an increase of 1,30% for the first scenario and a decrease of 0,69% for the second scenario. The sedimentation increased for the first scenario 2,80% but for the second scenario it decreased by 1,95%. By changing the forest cover of a site the water dynamics are modified generating an impact on the production of water, flow and sediment.
Tesis de Graduación (Licenciatura en Ingeniería Forestal) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2018.
Keywords: Modelo SWAT; Agua; Residuos; Cobertura forestal; Research Subject Categories::NATURAL SCIENCES::Earth sciences::Atmosphere and hydrosphere sciences::Hydrology